Geographic Information Engineering and Social Ground Truth in Attappadi, Kerala State, India - Wolfgang Hoeschele (Annals of the Association of American Geographers , 90(2), 2000, p. 293-321, 2000)
The use of geographic information systems (GIS) and related technologies by private organizations or government agencies toward applied objectives may be defined as geographic information engineering (GIE). GIE is particularly well adapted to certain types of institutions and user groups, who can use it as an instrument of power over those people who have little or no access to the technology. In the case of Attappadi, a region in the Western Ghats of Kerala, India, a state agency has employed GIE in such a way that it obscures the fact that land-cover data have been substituted for land-usedata, which were never collected in the first place. Their analysis, based predominantly on satellite vegetation cover data, greatly overstates the amount of wastelands in the region, and consequently minimizes the productive roles of peasants and adivasis (tribals) in managing the land. This abuse of the power of GIE could be rectified technically by adding layers uses, and institutionally by a more participatory process of GIE. Such a response, however, is unlikely as long as governmental attitudes toward peasant and adivasi knowledge remain fundamentally unchanged, and the requisite levels of formal education are largely absent in the population affected. This demonstrates that technologies such as GIS must be evaluated not only in terms of technical measures of efficiency, but also in terms of social process